2021
DOI: 10.1371/journal.pmed.1003832
|View full text |Cite
|
Sign up to set email alerts
|

Educational and health outcomes of schoolchildren in local authority care in Scotland: A retrospective record linkage study

Abstract: Background Looked after children are defined as children who are in the care of their local authority. Previous studies have reported that looked after children have poorer mental and physical health, increased behavioural problems, and increased self-harm and mortality compared to peers. They also experience poorer educational outcomes, yet population-wide research into the latter is lacking, particularly in the United Kingdom. Education and health share a bidirectional relationship; therefore, it is importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 41 publications
1
22
0
Order By: Relevance
“…These disproportionate changes to planned hospital care for vulnerable adolescents are likely to have contributed to further widening of the inequalities 15 that already existed before the pandemic, in terms of health, education and social care outcomes. 7 8 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These disproportionate changes to planned hospital care for vulnerable adolescents are likely to have contributed to further widening of the inequalities 15 that already existed before the pandemic, in terms of health, education and social care outcomes. 7 8 …”
Section: Discussionmentioning
confidence: 99%
“…Based on this framework, we hypothesised that adolescents receiving children’s social care (CSC) services or special educational needs (SEN) support were likely to have been more affected by the large reductions in planned hospital care during the pandemic as they have higher rates of chronic health conditions than their peers. 7 8 …”
Section: Introductionmentioning
confidence: 99%
“…Data on outcomes in the existing literature is patchy with varied outcomes measured; further, they often lack an economic analysis (Edmunds et al., 2018). However, children subject to welfare systems, internationally, tend to have poorer physical and mental health, educational and criminal justice outcomes than others but robust, comparative research seems unlikely to focus on secure settings (Fleming et al., 2021; Kaariala & Hiilamo, 2017; Porter et al, 2020). Children in secure hospitals are usually returned to the wider community (Livanou et al., 2020) but longer term outcomes are less clear.…”
Section: The Status Of Interventionsmentioning
confidence: 99%
“…Fleming et al also reported no significant difference in asthma prevalence (after adjustment for birth and socioeconomic factors) in their population-level administrative health data study of school-aged children. 19 Reviewing the available literature can help to clarify such ambiguities. There is, of course, some risk that differences between care-experienced and other children in the prevalence of diagnosed health conditions are due to differences in health-seeking behaviour rather than truly better health.…”
Section: Introductionmentioning
confidence: 99%
“…Hospitalisations due to both injury and self-harm have been found to be more common in school-aged children in care than in their non-care peers, after adjusting for a range of socioeconomic and maternal factors. 19 Neglectful parenting also has consequences for conditions where proactive health behaviours are vital. For example, dental health problems were significantly more frequently identified in children in care than in the general population during a universal dental health screening programme in Scotland.…”
Section: Introductionmentioning
confidence: 99%